New Techs and Trends in Gastronomy - Çalışkan, Serkan (Emerald Publishing Limited, 2024)
Abstract In this chapter, a situation analysis was made on the use of technology in gastronomy, an ever-growing and exciting research area. The use of technology is essential in food production processes as well as in all sectors, and accordingly, the number of research on the subject has increased in recent years. Therefore, in the study, information is also given about trend applications today in addition to the use of technology in gastronomy. It is aimed to present the studies conducted by different disciplines together, to reveal the current situation in the light of the studies carried out on a national and international scale and to support possible future studies.